Pleiotropic Effects of Bacterial Small Alarmone Synthetases: Underscoring the Dual-Domain Small Alarmone Synthetases in Mycobacterium smegmatis - Krishnan, Sushma; Chatterji, Dipankar (Frontiers in Microbiology, 2020)
The nucleotide alarmone (p)ppGpp, signaling the stringent response is known for more than five decades. The cellular turnover of the alarmone is regulated by RelA/SpoT homolog (RSH) superfamily of enzymes. They are long RSH (RelA, SpoT, and Rel) and short RSH [small alarmone synthetases (SAS) and small alarmone hydrolases (SAH)]. Long RSHs are multidomain proteins with (p)ppGpp synthesis, hydrolysis, and regulatory functions. Short RSHs are single-domain proteins with a single (p)ppGpp synthesis/hydrolysis function with few exceptions having two domains. Mycobacterial RelZ is a dual-domain SAS with RNase HII and the (p)ppGpp synthetase activity. SAS is known to impact multiple cellular functions independently and in accordance with the long RSH. Few SAS in bacteria including RelZ synthesize pGpp, the third small alarmone, along with the conventional (p)ppGpp. SAS can act as an RNA binding protein for the negative allosteric inhibition of (p)ppGpp synthesis. Here, we initially recap the important features and molecular functions of different SASs that are previously characterized to understand the obligation for the “alarmone pool” produced by the long and short RSHs. Then we focus on the RelZ, especially the combined functions of RNase HII and (p)ppGpp synthesis from a single polypeptide to connect with the recent findings of SAS as an RNA binding protein. Finally, we conclude with the possibilities of using ssRNA as an additional therapeutic strategy to combat the persistent infections by inhibiting the redundant (p)ppGpp synthetases.